Fuzzy model for evaluation of selected Diabetes Medical Sites - Abed, Majida Ali; Alasadi, Hamid Ali Abed (IJRDO -Journal of Computer Science Engineering, 2016)
The aim of this paper is to give model to evaluate Diabetes Medical Sites (DMSs) quality byfuzzy system to arrange these sites according to their quality depending on the values that get itduring the application of the model on these sites. This model contain the most importantelement suggested for quality criteria like the Design Site, Update Site, Hyperlinks, Ability ofUser, Insufficient, Information, Use of visual effects, Data on the sources, time Input,Consistency content with goals of site. The particular goals of this work were to identify criteriafor the evaluation of DMSs such as legitimacy; dependability, and usefulness and find out theweakness of those sites. The particular goals of this work were to identify criteria for theevaluation of DMSs, reconnoiter; usability of recognize criteria for the evaluation of DMSs withthe identified criteria for the corroboration; of legitimacy; dependability, and usefulness; and findout the weakness of those sites. Additional, we give propositions; for improving the usability,content quality, dependability, performances and some other elements that must took care whenevaluating sites and documentation information can use it in scientific research.